VODKA-JWST: a 3.8 kpc dual quasar at cosmic noon in a powerful starburst galaxy with JWST/MIRI integral field unit - Chen, Yu-Ching; Ishikawa, Yuzo; Zakamska, Nadia L.; Liu, Xin; Shen, Yue; Hwang, Hsiang-Chih; Rupke, David; Vayner, Andrey; Gross, Arran C.; Liu, Weizhe; Wylezalek, Dominika; Veilleux, Sylvain; et al. (The astrophysical journal, 2024)
Dual quasars - two active supermassive black holes at galactic scales - represent crucial objects for studying the impact of galaxy mergers and quasar activity on the star formation rate (SFR) within their host galaxies, particularly at cosmic noon when SFR peaks. We present JWST/MIRI mid-infrared integral field spectroscopy of J074922.96+225511.7, a dual quasar with a projected separation of 3.8 kpc at a redshift z = 2.17. We detect spatially extended [Fe ii] 5.34 μm and polycyclic aromatic hydrocarbon (PAH) 3.3 μm emissions from the star formation activity in its host galaxy. We derive the SFR of 103.0±0.2 M ⊙ yr−1 using PAH 3.3 μm, which is 5 times higher than that derived from the knee of the infrared luminosity function for galaxies at z ∼ 2. While the SFR of J0749+2255 agrees with that of star-forming galaxies of comparable stellar mass at the same redshifts, its molecular gas content falls short of expectations based on the molecular Kennicutt-Schmidt law. This discrepancy may result from molecular gas depletion due to the longer elevated stage of star formation, even after the molecular gas reservoir is depleted. We do not observe any quasar-driven outflow that impacts PAH and [Fe ii] in the host galaxy based on the spatially resolved maps. From the expected flux in PAH-based star formation, the [Fe ii] line likely originates from the star-forming regions in the host galaxy. Our study highlights the extreme stardust nature of J0749+2255, indicating a potential connection between the dual quasar phase and intense star formation activities.